Carta do Cônsul em Cantão, Demétrio Cinatti, para o Ministério de Negócios Estrangeiros sobre a questão das “dependências” de Macau, incluindo a questão de Hainan (1891)
This 1891 diplomatic dispatch, originating from the Portuguese Consulate in Canton and addressed to a high-ranking official in Lisbon, constitutes a formal report on political, administrative, and territorial tensions between Portuguese and Chinese authorities concerning Macau and its dependencies. The document details the shifting stance of local Chinese officials following communications from the Portuguese Ministry of the Navy, noting a cessation of objections to consular requests for interpreters. It highlights the influence of Viceroy Chang-chi-ting—a key anti-European figure—and his role in formulating opposition to Portuguese interests, particularly through a memorial submitted during Sino-Portuguese treaty negotiations. The text raises concerns over Chinese encroachment on Macau’s jurisdiction, citing the arrest of bailiffs on Taipa Island and the circulation of administrative notices asserting Chinese authority over local populations. Reference is made to the Green Island (Ilha Verde) dispute as precedent for covert jurisdictional claims. The author warns against potential threats to Coloane and Taipa, where Portuguese military presence remains limited amidst a significantly larger Chinese population. Administrative practices, including falsified inspection reports submitted to the Tsung-li Yamen, are presented as evidence of systematic efforts to erode Portuguese control. Additional matters include unresolved diplomatic notes on Hainan, delays in Sino-Portuguese negotiations, persecution of French Catholic missions in northern China attributed to anti-Manchu secret societies, and observations on rice trade dynamics affecting Macau. The document provides critical insight into colonial diplomacy, jurisdictional contestation, and power asymmetries in late 19th-century South China.
2
Keywords: Chinese authorities shifting stance; Coloane jurisdiction threat; Consular Interpreters Requests; Consular Relations 1891; Green Island dispute; Hainan jurisdiction impact; Historical Diplomatic Correspondence; Macau territorial dispute; Navy Ministry communications; Portuguese Consulate in Canton; Portuguese interests opposition; Power Asymmetries Contestation; Secret Societies Observations; Sino-Portuguese treaty negotiations; Systematic Efforts Evidence; Taipa Island bailiffs arrest; Transcription; Verde dispute precedent; Viceroy Chang-chi-ting; administrative conflicts Macau; administrative notices Chinese authority; colonial governance Macau; dependencies of Macau; political tensions Portugal China